TINGKAT KECERDASAN INTERPERSONAL MAHASISWA BK STKIP PGRI SUMATERA BARAT (Studi terhadap Mahasiswa Angkatan 2011) - Zilkifli, Ira; Ibrahim, Indra; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This study is based on field problem, which is still a counseling student are less skilled in socializing and interacting with the environment. the researchers raised concerns about the research: how the interpersonal intelligence counseling students in STKIP PGRI Sumatera Barat. The purpose of this study was to describe the ability of students to socialize and empathize. This research is a descriptive study. The study population was all students counseling class of 2011 in STKIP PGRI Sumatera Barat and sampling technique is proportional rondom sampling, sample size was 51 of 330 students. The instrument used was a questionnaire and techniques to analyze the data by percentage. Results of this study, in general the interpersonal intelligence counseling students class of 2011 are smart, social skills and empathy as well as smart. However, ability to speak and communicative empathyÂ is smart enough and the habit of hearing less smart. Based on the study results, the authors suggest counseling students to improve his interpersonal intelligence. The manager of guidance and counseling department in STKIP PGRI Sumatera Barat to further enhance students competence.